TANTANGAN DAN KESULITAN SIBLING DARI INDIVIDU BERKEBUTUHAN KHUSUS - Nur, Haerani; Zainuddin, Kurniati (Universitas Islam Negeri Alauddin Makassar, 2023)
Sibling is one of the important sources of support in families with individuals with special needs, but sometimes they may not be able to fulfill their roles effectively due to various challenges and difficulties they face. This study aims to explore the challenges and difficulties experienced by siblings of individuals with special needs. A search for research articles was conducted using keywords such as